Wealth Effects on Consumption in a Modified Life-Cycle Model - Deaton, A. S. (Review of Economic Studies, 1972)
Journal Article Wealth Effects on Consumption in a Modified Life-Cycle Model Get access A. S. Deaton A. S. Deaton Department of Applied Economics, Cambridge Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 39, Issue 4, September 1972, Pages 443–453, https://doi.org/10.2307/2296512 Published: 01 September 1972